2013
DOI: 10.3390/molecules181011733
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Origin and Biological Source on Chemical Composition, Anticholinesterase and Antioxidant Properties of Some St. John’s Wort Species (Hypericum spp., Hypericaceae) from the Central Balkans

Abstract: Abstract:The study shows the influence of the origin of plant material and biological source on the in vitro antioxidant (neutralization of DPPH and OH radical, nitric oxide, and inhibition of lipid peroxidation) and anticholinesterase activity of chemically characterized and quantified ethanol extracts of ten St. John's wort samples. The investigated samples were: five Hypericum perforatum species representatives collected at different localities, one commercial sample of Hyperici herba purchased at a local m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 36 publications
(88 reference statements)
12
63
1
Order By: Relevance
“…This was in line with the results on the Y TP and consisted clear evidence that differences in Y TP were reflected on the antioxidant properties of the extracts. This assumption is in accordance with previous examinations on various Hypericum species, where it was shown that extracts with higher polyphenolic load also exhibited stronger antioxidant effects [24,25]. Similar results were reported for several Hypericum taxa [26][27][28].…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…This was in line with the results on the Y TP and consisted clear evidence that differences in Y TP were reflected on the antioxidant properties of the extracts. This assumption is in accordance with previous examinations on various Hypericum species, where it was shown that extracts with higher polyphenolic load also exhibited stronger antioxidant effects [24,25]. Similar results were reported for several Hypericum taxa [26][27][28].…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…These results suggest that HPE could have some beneficial effects on alcohol withdrawal syndrome in people [102]. Hypericum perforatum exhibits remarkable antioxidant potential due to high content of phenolic compounds, especially flavonoids, hyperforin and hypericin [103]. Hyperforin has NMDA-receptor-antagonistic and potential neuroprotective effects in vitro which might provide therapeutic effectiveness in the relapse prevention of alcohol use disorders [103].…”
Section: Hypericum Perforatummentioning
confidence: 92%
“…Hypericum perforatum exhibits remarkable antioxidant potential due to high content of phenolic compounds, especially flavonoids, hyperforin and hypericin [103]. Hyperforin has NMDA-receptor-antagonistic and potential neuroprotective effects in vitro which might provide therapeutic effectiveness in the relapse prevention of alcohol use disorders [103]. In addition, hyperforin could reduce alcohol intake more effectively than hypericin in alcohol-dependent mice [104].…”
Section: Hypericum Perforatummentioning
confidence: 99%
“…1,19,21 The polycyclic dione hypericin (HY), which is one of the active ingredients of St John's wort, is a photosensitizer that accumulates in dark glands found in flowers and leaves. [22][23][24] HY has been proposed as a highly promising photosensitizer due to its minimal toxicity, tumor high selectivity, high clearance from the host body, much singlet oxygen production and anti-inflammatory properties, as HY is able to induce the apoptosis of human lens epithelial cells, nasopharyngeal carcinoma cells, and U87 glioma cells 20,23,[25][26][27][28] during the rapid healing process after PDT. However, the effectiveness of HY as a potential sonosensitizer for SDT remains relatively unknown.…”
Section: Introductionmentioning
confidence: 99%